Tiempos, espacios y memorias: diálogos interculturales con docentes de la provincia de Huíla en Angola (2021)
This article is the result of a postdoctoral research conducted at the Instituto Superior de Ciencias da Educação (Isced) of Lubango, in Angola. We aim to identify how experiences, memories, heritage, and local cultures are handled in the production of school knowledge, based on the research work in basic education institutions in seven municipalities in the province of Huila. For the collection of the information, we work with various documents and oral interviews with fifteen teachers. Theoretically, we dialogue with decolonial epistemology, interculturality, oral history, memory, cultural heritage, and local history. In this article, we present some narratives about the contents taught concerning local knowledge. The article presents an introduction, a brief discussion about interculturality and education, geohistorical records on Angola, memories and narratives, and final reflections.